Corrosive Esophageal Injury due to a Commercial Vinegar Beverage in an Adolescent - Jiyeon Chang; Sang Eun Han; Seung Sam Paik; Yong Joo Kim (Korean Society of Gastrointestinal Endoscopy, 2020)
Although gastroesophageal damage is commonly induced by accidental drinking of a strong acid or alkali, damage due to the consumption of a vinegar beverage is not well known. We report a case of corrosive esophageal ulcer found in an adolescent consuming a vinegar drink daily. A 15-year-old male visited the emergency room presenting with hematemesis and severe epigastric pain. Multiple longitudinal ulcers, concurrent mucosal hemorrhage, and denuded mucosa were noted in the whole of the esophagus via an endoscopic examination. He had been drinking a vinegar beverage daily without sufficient dilution. The patient was treated with corticosteroid, antibiotic therapy, and mucosa protecting alginate medication and was asked to fast for a week. The follow-up endoscopy showed improvements of the esophageal injuries. Overall, continuous consumption of a vinegar beverage can result in acidic burns and destruction of the surface of the upper gastrointestinal tract. Therefore, vinegar beverages should be considered as corrosive agents.